Design and assessment of a 360° panoramic and high-performance capture system with two tiled catadioptric imaging channels - Song, Weitao (2019)
It has always been a challenge to obtain a 360° panoramic imaging system with a high-resolution and non-visible seam. In this study, a 360° panoramic and high-performance system has been developed based on two tiled imaging channels with a field of view of 190° and /# of 2.0. In this study, some issues regarding 360° panoramic tiled methods, such as relative illuminance and ghost images, were analyzed in detail and taken into consideration during the design procedure. In the final design, the stop has been fulfilled for each field angle, and the ghost images have also been well optimized. A proof-of-concept prototype producing a high-performance 360° panoramic video has been developed.